Problematizing truth-telling in a post-truth world: Foucault, parrhesia, and the psycho-social subject - Ambrosio, John (Educational philosophy and theory, 2022)
The study examines how truth-tellers and truth-telling can be cultivated in the context of post-truth politics in the U.S. Following Foucault, it is not concerned with examining the problem of truth, with the philosophical question of how truth is determined, but with the problem of truth-tellers or truth-telling as a practical activity of self-improvement. To this end, the study traces the emergence and nature of post-truth politics in the U.S. and analyzes its relation to patterns of fascist propaganda and the psychological appeal of authoritarian leaders through a psycho-social perspective. To counter the nature and ubiquity of post-truth politics, the unrelenting flow of lies, disinformation, and conspiracy theories disseminated by the far-right news and information ecosystem, the author argues that educators can help students recognize truth-tellers and become truth-tellers themselves by employing certain pedagogical strategies, informed by Foucault's analysis of parrhesia, that can equip them to criticize and resist post-truth propaganda and demagogues.